The landscape of N6-methyladenosine modification patterns and altered transcript profiles in the cardiac-specific deletion of natriuretic peptide receptor A. (22nd November 2022) - Shen, Xi; Chang, Pan; Zhang, Xiaomeng; Zhang, Jing; Wang, Xihui; Quan, Zhuo; Wang, Pengli; Liu, Tian; Niu, Yan; Zheng, Rong; Chen, Baoying; Yu, Jun
Abstract : By conjoint analysis of m6A modification patterns and transcript profiles in cardiac NPRA CKO mice, we show that Pdk4 and its m6A modification might be crucial regulators in metabolic imbalance and insulin resistance impacted by NP signalling. Abstract : The atrial natriuretic peptide (ANP) and the brain natriuretic peptide (BNP) are critical biological makers and regulators of cardiac functions. Our previous results show that NPRA (natriuretic peptide receptor A)-deficient mice have distinct metabolic patterns and expression profiles compared with the control. Still, the molecular mechanism that could account for this observation remains to be elucidated. Here, methylation alterations were detected by mazF-digestion, and differentially expressed genes of transcriptomes were detected by a Genome Oligo Microarray using the myocardium from NPRA-deficient (NPRA −/− ) mice and wild-type (NPRA +/+ ) mice as the control. Comprehensive analysis of m6A methylation data gave an altered landscape of m6A modification patterns and altered transcript profiles in cardiac-specific NPRA-deficient mice. The m6A "reader" igf2bp3 showed a clear trend of increase, suggesting a function in altered methylation and expression in cardiac-specific NPRA-deficient mice. Intriguingly, differentially m6A-methylated genes were enriched in the metabolic process and insulin resistance pathway, suggesting a regulatory role in cardiac metabolism of m6A modification regulated by NPRA. Notably, it was confirmed that the pyruvate dehydrogenase kinase 4 (Pdk4) gene upregulated the gene expression and the hypermethylation level simultaneously, which may be the key factor for the cardiac metabolic imbalance and insulin resistance caused by natriuretic peptide signal resistance. Taken together, cardiac metabolism might be regulated by natriuretic peptide signaling, with decreased m6A methylation and a decrease of Pdk4.